2020
DOI: 10.48550/arxiv.2009.13319
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extension of Gyarfas-Sumner conjecture to digraphs

Abstract: The dichromatic number of a digraph D is the minimum number of colors needed to color its vertices in such a way that each color class induces an acyclic digraph. As it generalizes the notion of the chromatic number of graphs, it has been a recent center of study. In this work we look at possible extensions of Gyárfás-Sumner conjecture. More precisely, we propose as a conjecture a simple characterization of finite sets F of digraphs such that every oriented graph with sufficiently large dichromatic number must… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Just as in the undirected case, Aboulker et al [1] observed several necessary conditions for a finite set F of digraphs to be heroic, which we summarize in the following. Proposition 1.3 (cf.…”
Section: Introductionmentioning
confidence: 96%
See 4 more Smart Citations
“…Just as in the undirected case, Aboulker et al [1] observed several necessary conditions for a finite set F of digraphs to be heroic, which we summarize in the following. Proposition 1.3 (cf.…”
Section: Introductionmentioning
confidence: 96%
“…In the same spirit, Aboulker, Charbit and Naserasr [1] recently initiated the systematic study of the relation between excluded induced subdigraphs and the dichromatic number and asked the following intriguing question. Problem 1.2.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations